2006
DOI: 10.1111/j.1399-5618.2006.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of risk factors for attempted suicide among patients with bipolar disorder

Abstract: During a medium-term follow-up, as many as one-fifth of random psychiatric patients with BD attempted suicide, which highlights the public health importance of suicidal behavior in BD. Previous suicide attempts, hopelessness and depressive phase were the key indicators of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
7
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 26 publications
(50 reference statements)
14
118
7
2
Order By: Relevance
“…Other studies did not find a relationship between rapid cycling and suicide attempts, 33,57 although rapid cycling was associated with other risk factors for suicidal behavior, such as early age of onset, more depressive episodes, and family history of bipolar disorder. 6) Comorbidity with Axis I and Axis II disorders Comorbidity is common among patients with bipolar disorder.…”
Section: ) Rapid Cyclingmentioning
confidence: 92%
See 3 more Smart Citations
“…Other studies did not find a relationship between rapid cycling and suicide attempts, 33,57 although rapid cycling was associated with other risk factors for suicidal behavior, such as early age of onset, more depressive episodes, and family history of bipolar disorder. 6) Comorbidity with Axis I and Axis II disorders Comorbidity is common among patients with bipolar disorder.…”
Section: ) Rapid Cyclingmentioning
confidence: 92%
“…32 Valtonen et al also showed that suicidal ideation was a predictor of suicide attempts in univariate analyses of a bipolar sample, but in a multivariate analysis, suicidal ideation was no longer a predictor of suicide attempts. 33 Galfavy et al demonstrated a strong correlation between higher levels of suicidal ideation and future attempts in bipolar samples. 34 Marangell et al, in a sample of 1,556 individuals with bipolar I and bipolar II, also showed that previous attempters reported more suicidal ideation at baseline and an increased risk for suicide attempts during follow-up.…”
Section: Stress-diathesis Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…This is close to ArsenaultLapierre et al, 2004 (9) who found that the risk of mood disorders, specifically, depressive disorders, are greater in female suicides, whereas mood disorders represented 59.4 % of the female diagnoses and 47.4 % of the male diagnoses. However, Valtonen et al, 2006 (10) reported that male gender is predominant in patients with bipolar disorder who attempt suicide. In patients with psychotic disorders, the results showed that schizoaffective disorder, brief psychotic disorder .schizophrenioform were slightly higher in females than males (13% -4.3% -2.2% -5.6% _ 0.0% respectively).…”
Section: Disscutionmentioning
confidence: 99%